Branding Pesantren Preuner dalam Memperkuat Identitas Kelembagaan - Mohammad Halili; Ach Rizquha; Hefniy Hefniy (Universitas Nurul Jadid, 2020)
The purpose of this study was to describe the branding of pre-employed Islamic boarding schools in strengthening the identity of the pesantren which was carried out by the Nurul Qarnain Sukowonojember Islamic Boarding School. The data in this study is primary data. This research method uses a qualitative approach with a case study method. This research focuses intensively on one particular object that is studied as a case. Data collection techniques through interviews and observation. The results showed that the branding of the Nurul Qarnain Prenuer Islamic Boarding School was with attributes, benefits, values, personality and users as the beneficiaries of the existence of the Nurul Qarnain Preamble Islamic Boarding School. Basically, the Nurul Qarnain Islamic Boarding School already has pre-employment boarding school branding in the community, this is evidenced by the large number of students who are at the Nurul Qarnain Islamic Boarding School. On the other hand, what has been done by Nurul Qarnain Islamic Boarding School in branding pre-employed boarding schools is more in the nature of development by sharpening specific aspects of the field of activity units which are supported by several specialization programs so as to strengthen the identity of the pesantren.